Trace Element Geochemistry of Magnetite and Accesory Phases from El Romeral Iron Oxide-Apatite Deposit, Northern Chile - Barra-Pantoja, Luis Fernando; Rojas, Paula A; Reich, Martín; Deditius, Artur; Simon, Adam
Iron oxide-apatite (IOA) or “Kiruna-type” deposits are an important source of Fe, P, REE, among other essential elements for society. Three main hypotheses have been proposed to explain the genesis of these controversial deposits, which invoke liquid immi